Novel canine circovirus strains from Thailand: Evidence for genetic recombination - Chutchai Piewbang (Nature Portfolio, 2018)
Abstract Canine circoviruses (CanineCV’s), belonging to the genus Circovirus of the Circoviridae family, were detected by next generation sequencing in samples from Thai dogs with respiratory symptoms. Genetic characterization and phylogenetic analysis of nearly complete CanineCV genomes suggested that natural recombination had occurred among different lineages of CanineCV’s. Similarity plot and bootscaning analyses indicated that American and Chinese viruses had served as major and minor parental viruses, respectively. Positions of recombination breakpoints were estimated using maximum-likelihood frameworks with statistical significant testing. The putative recombination event was located in the Replicase gene, intersecting with open reading frame-3. Analysis of nucleotide changes confirmed the origin of the recombination event. This is the first description of naturally occurring recombinant CanineCV’s that have resulted in the circulation of newly emerging CanineCV lineages.